Mild KCC2 Hypofunction Causes Inconspicuous Chloride Dysregulation that Degrades Neural Coding - Doyon, Nicolas; Prescott, Steven A.; De Koninck, Yves (Frontiers in Cellular Neuroscience, 2016)
Disinhibition caused by Cl- dysregulation is implicated in several neurological disorders. This form of disinhibition, which stems primarily from impaired Cl- extrusion through the co-transporter KCC2, is typically identified by a depolarizing shift in GABA reversal potential (EGABA). Here we show, using computer simulations, that intracellular [Cl-] exhibits exaggerated fluctuations during transient Cl- loads and recovers more slowly to baseline when KCC2 level is even modestly reduced. Using information theory and signal detection theory, we show that increased Cl- lability and settling time degrade neural coding. Importantly, these deleterious effects manifest after less KCC2 reduction than needed to produce the gross changes in EGABA required for detection by most experiments, which assess KCC2 function under weak Cl- load conditions. By demonstrating the existence and functional consequences of “occult” Cl- dysregulation, these results suggest that modest KCC2 hypofunction plays a greater role in neurological disorders than previously believed.